Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1211/0022357001773841
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Metabolism of the Monoterpene Carvone by Rat and Human Liver Microsomes

Abstract: The large amounts of carvone enantiomers consumed as food additives and in dental formulations justifies the evaluation of their biotransformation pathway. The in-vitro metabolism of R-(-)- and S-(+)-carvone was studied in rat and human liver microsomes using chiral gas chromatography. Stereoselective biotransformation was observed when each enantiomer was incubated separately with liver microsomes. 4R, 6S-(-)-Carveol was NADPH-dependently formed from R-(-)-carvone, whereas 4S, 6S-(+)-carveol was produced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…First, we investigated the possibility of sedative effects of the odor of jasmine tea at low intensity in comparison with the odor of lavender because this has been shown pharmacologically to have sedative effects in animals and humans (Buchbauer et al 1991;Hardy et al 1995;Lis-Balchin and Hart 1997a) and it includes a component, (R)-())-linalool, also found in jasmine tea (Ito et al 2002). Second, we investigated whether these effects were caused directly by (R)-())-linalool, and whether its optical isomer (S)-(+)-linalool has the same effects because differing pharmacological effects have been reported for the optical isomers of volatile components (Jager et al 2000(Jager et al , 2001Laska et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…First, we investigated the possibility of sedative effects of the odor of jasmine tea at low intensity in comparison with the odor of lavender because this has been shown pharmacologically to have sedative effects in animals and humans (Buchbauer et al 1991;Hardy et al 1995;Lis-Balchin and Hart 1997a) and it includes a component, (R)-())-linalool, also found in jasmine tea (Ito et al 2002). Second, we investigated whether these effects were caused directly by (R)-())-linalool, and whether its optical isomer (S)-(+)-linalool has the same effects because differing pharmacological effects have been reported for the optical isomers of volatile components (Jager et al 2000(Jager et al , 2001Laska et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome P450 (P450 1 ) enzymes in liver microsomes of these animal species have been shown to oxidize limonene to several oxidation products such as 1,2-and 8,9-epoxides, carveol (a product by 6-hydroxylation), perillyl alcohol (a product by 7-hydroxylation) (Watabe et al, 1980(Watabe et al, , 1981Jager et al, 1999). Recently we reported that limonene enantiomers are oxidized to carveols and perillyl alcohols by CYP2C11 in liver microsomes of untreated rats and by CYP2B1 in those of phenobarbital-treated rats (Miyazawa et al, 2002).…”
mentioning
confidence: 99%
“…In general, metabolic biotransformation of EO compounds occurs in two phases and the final products are glucuronide and sulfate conjugates (Jager 2000). Although the liver is considered the most important organ for biotransformation, Raoof et al (1996) and Shipkova et al (2001) in their studies demonstrated more effective glucuronidation of phenolic compounds in kidney than in liver or intestinal microsomes.…”
Section: Discussionmentioning
confidence: 99%